Study of Water Quality and Some Minerals from Consumer Source in the Community of Bor Nam Ron, Amphoe Betong, Yala Province - จาเอาะ ดาริกา; อินตัน ไมมูน; เจ๊ะลี อามีนี (YRU Journal of Science and Technology, 2019)
Hot springs water quality in Amphoe Betong, Yala during July to October 2017 was studied. The results of the water quality analysis were compared with the surface water quality according to the based on the National Environmental Board in 1994. With the amount of Copper, Manganese, Cadmium, Lead, Mercury, Arsenic, Total coliform bacteria, Dissolved oxygen, Nitrate -nitrogen and Ammonia-nitrogen were found in the Reservoir, the water quality was classified in category 2-3 suitable for household consumption but need a proper process of water treatment. From the study on certain minerals existing inside the hot spring, the comparison was compared with the standards of natural mineral water announced by Department of Health, Ministry of Public Health (2000) and against with the Standard of Mineral Water by Standard Industrial Product Mineral Water(TISI 2208-2004). We found that the amount of fluorine, pH and total hardness exceeded the prescribed standard. In addition, more harmful minerals such as Cadmium, Lead and Mercury were also found. While the amount of minerals in the hot spring such as Chloride, Potassium, Sodium and Iron were also found with the amount that suitable for producing mineral water in spa industry.